Profil Penilaian Kognitif Online Materi Matriks Berbasis LMS Moodle - Nugroho, Wachid (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2022)
Online distance learning (PJJ) has been going on for more than a year. One of the cognitive assessment models to evaluate students learning outcomes in the PJJ process is using the LMS Moodle. The aims of this research were to: 1)determine the implementation of cognitive assessment in the form of multiple choice matrix material for class XI SMA/SMK using LMS Moodle, and 2) find out student responses and perceptions and also what students did in the online cognitive assessment. This research method uses descriptive qualitative method. The data collection technique uses observation and documentation techniques on the results of the assessment and indirect interviews wirh students. The non-probability sample interviewed was 143 students taken by quota sampling in class XI DPIB A and B, XI TKJ A and B SMK Negeri 2 Salatiga for the 2021-2022 academic year from a total of 18 classes (635 student). Data analysis was carried out descriptively after the data was sorted and grouped based on the category of each student’s answer. The result obtained from this research indicate that 50,4% of students are ready to face the assessment and 69,3% of students are disciplined in working, 77,6% of students are fluent in accessing the assessment but only 20,3% of students are honest in working without opening notes and or collaborating with other students, 95,9% of students stated that the qustions werw in accordance with the material being taught. In general, the online cognitive assessment of the matrix material based LMS Moodle is practical, effective, easy to use and can be applied to other mathematics materials and other subjects.